Myth and Discourse in Portuguese Press on 500 aniversary commemorations - Kristensen, Barbara; Pim, Joam Evans (Brazilian journalism research, 2005)
The kind of colonization that the ﬁ fteenth-century Portuguese State applied in Brazil, colonization based on exploitation, certainly had some inﬂ uence on the construction of “Brazilian-ness” in relation to Portugal and “Portuguese-ness” in relation to Brazil. The 500th Anniversary of the Discovery, much celebrated both in the European ﬁ nisterrae and in the terra brasilis, is undoubtedly a unique opportunity to recreate and revise concepts, prejudices and representations of the relations built over the past ﬁ ve centuries. This paper presents some of the ﬁ ndings of the research of issues of the Portuguese daily newspapers Público, Diário de Notícias and Jornal de Notícias published between January and June 2000, regarding the commemoration of the 500th Anniversary of Cabral’s casual “visit” to Brazil. The purpose is to provide a description of the news discourses.